EFISIENSI PRODUKSI WORTEL DI DESA TULUNGREJO KECAMATAN BUMIAJI KOTA BATU - Waty, Klaudia Rewinda; Pudjiastuti, Agnes Quartina; Kholil, A. Yusuf (Agridevina : Berkala Ilmiah Agribisnis, 2021)
ABSTRACT Carrots are one type of vegetable that can be planted throughout the year, but their production tends to fluctuate due to various factors, including the use of inputs. Efforts to increase commodity production are intended to improve land productivity and farmers' income. The aim of this study was to analyze efficiency of carrot (Daucus carota L.) production in Tulungrejo Village. The village is one of the carrot production centers in Batu City which administratively belongs to the Batu District area. Data collection was carried out through interviews with 30 farmers. Data that has been collected in the field, first edited, then tabulated and analyzed with Cobb-Douglas production function. Production function used is an appropriate model because the coefficient of determination is close to one and meets requirements of classical assumption test (normal spread data, no multicollinearity and heteroscedasticity). The results showed that area of ​​land, seeds, manure, urea and urea fertilizer had a significant and positive effect on carrot production, while TSP fertilizer, labor and pesticides had no significant effect. In addition, all of input use by carrot farmers in Tulungrejo Village, Bumiaji District, Batu City is not economically efficient. It becomes a guideline for carrot farmers to evaluate the use of inputs for optimal production.Key words: efficiency, production, carrots, economic INTISARIWortel merupakan salah satu jenis sayuran yang dapat ditanam sepanjang tahun, tetapi produksinya cenderung berfluktuasi yang disebabkan oleh berbagai faktor, di antaranya berkaitan dengan penggunaan input. Upaya meningkatkan produksi komoditas ini dimaksudkan untuk memperbaiki produktivitas lahan dan pendapatan petani. Tujuan penelitian ini adalah menganalisis efisiensi produksi wortel ( Daucus carota L.) di Desa Tulungrejo. Desa ini merupakan salah satu sentra produksi wortel di Kota Batu yang secara administratif termasuk ke dalam wilayah Kecamatan Batu. Pengumpulan data dilakukan melalui wawancara dengan 30 petani. Data yang telah dikumpulkan di lapang, diedit terlebih dahulu, kemudian ditabulasi dan dianalisis dengan fungsi produksi Cobb-Douglas. Fungsi produksi yang digunakan merupakan model yang sesuai karena koefisien determinasinya mendekati satu dan memenuhi persyaratan uji asumsi klasik (data menyebar normal, tidak terjadi multikolinieritas dan heteroskedastisitas). Hasil penelitian menunjukkan bahwa luas lahan, benih, pupuk kandang, pupuk urea dan pupuk urea berpengaruh signifikan dan positif pada produksi wortel, sedangkan pupuk TSP, tenaga kerja dan pestisida tidak berpengaruh signifikan. Selain itu, seluruh penggunaan input oleh petani wortel di Desa Tulungrejo Kecamatan Bumiaji Kota Batu tidak efisien secara ekonomis. Ini menjadi pedoman bagi petani wortel untuk mengevaluasi penggunaan input-input tersebut agar produksinya optimal.Kata kunci: efisiensi, produksi, wortel, ekonomis DOI : https://doi.org/10.33005/adv.v10i2.2759